The Aiud “Prison Saints.” History, Memory, and Lived Religion - Grigore, Monica (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2015)
After the fall of communism in 1989, Romania, as others countries from Central and Eastern Europe, had to deal with its recent past marked by two dictatorships, one on the extreme right, the other on the extreme left. However, it seems that the post-communist society is rather preoccupied by the consequences of the communist regime than the fascist one. As the anti-communist narrative has become mainstream since the beginning of the 2000s, the victims of communist prisons received more and more attention. Several voices asked for the canonization of those prisoners that distinguished themselves for their belief. The Aiud “prison saints” are part of this current. Their stories are not simple and neither is the history: some of those who died in communist prisons were affiliated to the extreme right in the 1930s and the 1940s. While the Orthodox Church avoids to discuss their canonization, the new “saints” became the object of a popular devotion, which gathers together not only believers, but also representatives of the Church and the civil society. This article explores what the devotion for “prison saints” represents in the lived religion. Following the pilgrims to Aiud monastery and narratives concerning the “prison saints,” it appears that their veneration is not “natural,” but rather the result of a construction. As it turns out, lived religion is a vehicle for values diverging from the official democratic discourse.